PERANCANGAN APLIKASI PENGARSIPAN AKTA TANAH DENGAN METODE FAST DI KANTOR NOTARIS & PPAT ELIS SETYAWATI, S. H., M. Kn. - Mochamad Adhari Adiguna, M.Kom (Jurnal Penelitian Ilmu komputer, 2023)
The design of the Land Deed Submission System with this Fast Method was built to facilitate the work process in managing land certificate archives, specially in the archive field at the existing Notary & PPAT Office of Elis Setyawati, SH, M.Kn to make computerized data processing more effective to assist the implementation of land certificate data processing. more accurate, effective and efficient. A land deed is a tool or means to convey written information from one party to another. Such information can be in the form of notices, statements, requests, reports, thoughts, questions, and so on. Currently, in making the administration of land certificate archives at the Notary Office & PPAT Elis Setyawati, SH, M.Kn, there are several obstacles such as making archive administration reports, especially when viewing reports according to the desired time period, searching for documents stored at this time is still difficult and takes time which is old. because they have to open old documents and find one meeting and often have difficulty when doing the final recapitulation in the required period, therefore the author provides a solution in the form of a filing system design to make it easier for employees to process archive administrative data and make it easier to create data and reports. In this study, researchers used the Fast method. The expected result is a system design that can make the search system more efficient and report generation easier and faster.